Favorable coagulation profile with fondaparinux after hip surgery in elderly patients - Kudrnová, Zuzana; Kvasnička, Jan; Kudrna, Karel; Mazoch, Jiří; Malíková, Ivana; Zenáhlíková, Zuzana; Sudrová, Magda; Brzežková, Radka (International journal of hematology, 2009)
Twenty-three patients with fondaparinux prophylaxis over 75 years of age who underwent hip fracture surgery were enrolled in the study. Fondaparinux sodium (2.5 mg) was administered subcutaneously 6 h postoperatively and then every 24 h for 28 days. Coagulation and inflammatory parameters were measured preoperatively, then 10 h, 2, 7, and 28 days postoperatively. Increased D-dimers, positive acute phase proteins, and IL-6, and decreased negative acute phase proteins were observed preoperatively (P < 0.05). Maximum values were reached 10 h postoperatively for IL-6 and D-dimer, and on postoperative days 2 and 7 for positive acute phase proteins (P < 0.05). Transferrin, prealbumin and antithrombin levels were lowest 10 h postoperatively and on postoperative day 2 (P < 0.05). Increased D-dimers, IL-6, and positive acute phase proteins, and decreased negative acute phase proteins persisted until postoperative day 28 (P < 0.05). Prothrombin fragments (F1 + 2) reached peak levels preoperatively and decreased gradually until postoperative day 28. Fondaparinux promoted the inhibition of thrombin generation, as documented by negative correlation between F1 + 2 and FXa inhibition (r = -0.46; P < 0.001). Fondaparinux-induced FXa inhibition increased gradually until postoperative day 28. This increase correlated positively with antithrombin activity (r = 0.4; P < 0.05). Fondaparinux prophylaxis counteracted pro-thrombogenic effect associated with hip fracture and subsequent surgery without severe bleeding complications.
Keywords: senioři; polysacharidy; Acute-Phase Proteins; senioři nad 80 let; mediátory zánětu; Time Factors; žilní tromboembolie; mužské pohlaví; Venous Thromboembolism; Factor Xa Inhibitors; vyšetření krevní srážlivosti; fondaparinux; Inflammation Mediators; Injections, Subcutaneous; Postoperative Complications; Aged, 80 and over; Hip Fractures; antikoagulancia; ženské pohlaví; Humans; proteiny akutní fáze; Anticoagulants; Blood Coagulation Tests; časové faktory; inhibitory faktoru Xa; Blood Coagulation; fraktury kyčle; injekce subkutánní; Fondaparinux; Female; Aged; Polysaccharides; pooperační komplikace; hemokoagulace; lidé; Male